Intraoral lipoma: case report and literature update (Research, Society and Development, 2021)
The aim of the present study was to report a lipoma case diagnosed in a male, black, 56-year-old patient, who presented with a nodular lesion. This pathological process was asymptomatic, well defined lesion, of softened consistency, covered by mucosa with an intact surface, yellowish in color and measuring approximately 2.5 cm. Its evolution was approximately 4 years and was located in the bottom of the lower vestibule, between teeth 32 and 34. In view of the clinical aspects, the diagnostic Lipoma hypothesis was raised. Thus, an excisional biopsy was performed and, in addition to the histopathological examination of the removed specimen, it was possible to confirm the clinical diagnosis of the lesion. The patient has had no signs of recurrence for 7 months. It is worth highlighting the need for careful anamnesis, in addition to knowledge about the clinical findings by the Dental Surgeon, which enables and also provides a correct therapeutic approach for this injury by these professionals.